FORMULASI DAN EVALUASI PASTA GIGI YANG MENGANDUNG EKSTRAK DAUN TEH HIJAU (Camellia sinensis L.) DAN KULIT JERUK KEPROK (Citrus reticulata Blanco.) - Hasrawati, A.; Julyani, Sri; Aztriana, Aztriana (As-Syifaa Jurnal Farmasi, 2024)
Dental caries is one disease that occurs both in children and adults. One of the dental caries pathogenic microbial found in cariogenic biofilm or plaques is Streptococcus mutans. Natural material is one of the alternatives which can be used to treat the disease, some of them are green tea and tangerine peel. Both contain antibacterial active components against the Streptococcus mutans. This research used the ethanol extract of green tea and tangerine peel. Activity test of both extracts showed inhibition on Streptococcus mutans and Porphyromonas gingivalis 1.6%; 3.25% and 6.4% by green extract and 20%, 25% and 30% by tangerine peel. The goal of the research was to formulate the extract ethanol of green tea and tangerine peel into pharmaceutically stable toothpaste. Toothpaste is a semisolid disperse system preparations that contain amounts of insoluble solid. One of the functions of toothpaste is to clean the teeth. Physical stability test has been done to obtain the most optimum preparations. Formulation and evaluation of physical properties including organoleptic, homogeneity, pH measurement, viscosity, foam height and spreadability. Optimation base result showed that 1% Na CMC is the most stable in consistency. The formulation then continued with formulation into preparations and carried out the stability test and physical evaluations. Based on storage condition and physical test results showed that the preparations were stable pharmaceutically.